2017
DOI: 10.1159/000485817
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil (Viagra®) Prevents Cox-1/ TXA2 Pathway-Mediated Vascular Hypercontractility in ApoE-/- Mice

Abstract: Background/Aims: The atherosclerotic apolipoprotein E-deficient (apoE-/-) mouse exhibits impaired vasodilation and enhanced vasoconstriction responsiveness. The objectives of this study were: a) to determine the relative contribution of cyclooxygenases (Cox-1 and Cox-2), thromboxane A2 (TXA2) and endothelin-1 (ET-1) to enhancing vascular hyperresponsiveness in this model of atherosclerosis and b) to investigate the beneficial effects of the phosphodiesterase 5 inhibitor sildenafil on this endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 73 publications
3
3
0
Order By: Relevance
“…The data is also consistent with COX-1 being the primary isoform related to endothelium-dependent contractions [9,17,33,34] and enhanced thromboxane A2 TP receptor-dependent vascular contractions being associated with metabolic diseases [32,35]. Together, COX-1/TXA2 pathway has been shown to mediate vascular hypercontractility linked to endothelial dysfunction in obesity [32] and experimental model of hyperlipidemia [36]. Thromboxane A2 TP receptor is coupled to guanine nucleotide-binding protein Gq in vascular smooth muscle (VSM) [37].…”
Section: Discussionsupporting
confidence: 59%
“…The data is also consistent with COX-1 being the primary isoform related to endothelium-dependent contractions [9,17,33,34] and enhanced thromboxane A2 TP receptor-dependent vascular contractions being associated with metabolic diseases [32,35]. Together, COX-1/TXA2 pathway has been shown to mediate vascular hypercontractility linked to endothelial dysfunction in obesity [32] and experimental model of hyperlipidemia [36]. Thromboxane A2 TP receptor is coupled to guanine nucleotide-binding protein Gq in vascular smooth muscle (VSM) [37].…”
Section: Discussionsupporting
confidence: 59%
“…The novelty of the present study is the demonstration of the impact of SIL on oxidative stress, through complementary assays. While traditional techniques only quantify cumulative oxidation of target molecules (lipids, proteins or DNA) without distinguishing among the direct contributors to oxidative stress, our data demonstrate that SIL reduces oxidative damage due to a direct reduction in •O 2 ‐ , H 2 O 2 and particularly, in •OH/OONO ‐ species, also contributing to an increase in NO bioavailability, as recently observed by our group and others in distinct experimental models 31‐33 . The sum of this evidence may help to explain the potential benefits of SIL as an interesting candidate for gastroprotective therapies.…”
Section: Discussionsupporting
confidence: 79%
“…The anti-inflammatory and anti-thrombotic features of aspirin, the only known irreversible inhibitor of platelet COX1, are primarily related to the suppression of PG and TXA2 synthesis [ 241 ]. In this context, a recent study demonstrated that the COX1/TXA2 pathway is a relevant contributor to vascular hypercontractility in atherosclerotic apoE deficient mice, and its pharmacological inhibition improves endothelial function [ 242 ]. Despite being a well-established therapy in cardiovascular disease, some aspects of aspirin treatment warrant further investigation, as reflected by a recent analysis demonstrating an interaction of body weight with the effectiveness of aspirin to prevent cardiovascular events [ 243 ].…”
Section: Aa Metabolome In Atherosclerosis and Cardiovascular Diseamentioning
confidence: 99%